2009
DOI: 10.1590/s0101-31222009000200004
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização e comportamento germinativo de sementes de Casearia sylvestris Swartz (SALICACEAE)

Abstract: RESUmo -Casearia sylvestris Swartz (Salicaceae), nome popular de guaçatonga ou chá-de-bugre é um arvore amplamente distribuída pelo Brasil e com uso fitoterápico pela população humana que a explora nos ambientes nativos. o objetivo do presente estudo foi fornecer informações sobre o período das fenofases reprodutivas, sua morfologia e germinação de sementes de C. sylvestris, avaliando a existência de variabilidade do comportamento germinativo em lotes de diferentes procedências. Sementes de duas procedências, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 5 publications
0
8
2
10
Order By: Relevance
“…Sprouting from root buds could represent an effective strategy of spatial reoccupation and vegetative propagation; moreover, sprout shoots have the potential to emerge at variable distances from the main trunk and become independent plants (Rodrigues et al 2004). Imatomi et al (2009) reported that C. sylvestris seeds exhibit a low germination rate under laboratory conditions, whereas the presence of root buds may explain the wide distribution and high population density of this species. Furthermore, the potential of these buds for vegetative reproduction would enable the use of root cuttings to restore degraded areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sprouting from root buds could represent an effective strategy of spatial reoccupation and vegetative propagation; moreover, sprout shoots have the potential to emerge at variable distances from the main trunk and become independent plants (Rodrigues et al 2004). Imatomi et al (2009) reported that C. sylvestris seeds exhibit a low germination rate under laboratory conditions, whereas the presence of root buds may explain the wide distribution and high population density of this species. Furthermore, the potential of these buds for vegetative reproduction would enable the use of root cuttings to restore degraded areas.…”
Section: Resultsmentioning
confidence: 99%
“…According to Little & Wadsworth (1964), under good conditions C. sylvestris is capable of flowering and fruiting in the second year of life, when it reaches about 1 m height. Imatomi et al (2009) observed that 77.8 % of C. sylvestris seeds were subjected to predation or aborted (unviable) and only 20% of the viable seeds sown in a greenhouse emerged. On the other hand, young root sprouts ensure the maintenance of the population, likely due to greater resistance to physical damage by root sprouts than by seedlings (Toivonen et al 2011) and to rapid development, because their resources are drawn from the main trunk which is already established.…”
Section: Resultsmentioning
confidence: 99%
“…Para determinadas espécies, o desempenho germinativo das sementes é favorecido por temperaturas constantes, como em Dimorphandra mollis Benth. (Pacheco et al, 2010), por alternância de temperatura, a exemplo de Croton floribundus Spreng (Abdo e Paula, 2006) e por insensibilidade ao regime de temperatura utilizado, como foi observado nas sementes de caesaria sylvestris Swartz (Imatomi et al, 2009) e campomanesia adamantium Camb. (Scalon et al, 2009).…”
Section: Introductionunclassified
“…However, responses to GA 3 in seed germination are dependent on the species studied and on the In vitro propagation of Casearia sylvestris Swartz (Salicaceae) 1195 concentrations used. In studies of in vitro seed germination of forest and/or fruit species, the use of GA 3 in the culture medium at different doses did not improve the performance of seed germination (CALGAROTO et al, 2007;IMATOMI et al, 2009;MENEZES et al, 2010). Aseptic seedlings obtained from in vitro germination of mature seeds on a photoperiod of 16 h were used as donors of nodal segments (cotyledon and apical) to study plant micropropagation, testing five combinations of NAA and BAP.…”
Section: Resultsmentioning
confidence: 99%
“…The high extraction of this species in natural areas both for use in folk medicine and for reforestation, promotes degradation of the native flora and ecosystem disturbances (IMATOMI et al, 2009). This process can be considered partially sustainable, since this species is not cultivated and there is little basic information about the propagation and production of viable plants.…”
Section: Introductionmentioning
confidence: 99%